2021
DOI: 10.1099/jmm.0.001325
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of carbapenem-resistant Enterobacteriaceae and emergence of tigecycline non-susceptible strains in the Henan province in China: a multicentrer study

Abstract: Introduction. Carbapenem-resistant Enterobacteriaceae (CRE) have been responsible for nosocomial outbreaks worldwide and have become endemic in several countries. Hypothesis/Gap Statement. To better understand the epidemiological trends and characteristics of CRE in the Henan province. Aim. We assessed the molecular epidemiological characteristics of 305 CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…The problem of AMR is increasing globally with the spread frequently striking healthcare settings due to the improper use of antimicrobials and inappropriate infection control practices. AMR risk is especially in low- and middle-income countries [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem of AMR is increasing globally with the spread frequently striking healthcare settings due to the improper use of antimicrobials and inappropriate infection control practices. AMR risk is especially in low- and middle-income countries [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Carbapenems have been the drugs of choice to cure critical VAP infections, although illogical and very common use of carbapenems has given rise to the emergence of CR-GNB strains. Resistance to carbapenems is mediated by a variety of mechanisms [ 4 ]. Carbapenemase enzymes, the most significant of these mechanisms, are β-lactamases that inactivate many β-lactam antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 Other STs, such as ST37, ST3627, ST2593, and ST2601, were also detected in 34 TNSKP strains, which was different from previous reports in Henan. 30 Our study is the first to report of ST3627, ST2593, and ST2601 K. pneumoniae with tigecycline-non-susceptible caused by clinical infection. PFGE results showed that the most prevalent clone type ST11-K14K64 (28/34, 82.4%) belongs to cluster A.…”
mentioning
confidence: 65%
“…CRKP is resistant to most of the commonly used antimicrobial agents, thus limiting treatment options and posing a serious threat to the global public health [8]. Carbapenemases are the main causes of multidrug resistance in CRKP and are classified into class A (KPC), class B (NDM, IMP, and VIM), and class D (OXA-48-like) [9]. In China and elsewhere, KPCs are major contributors to carbapenem resistance in K. pneumoniae and more than 70% of carbapenemase-producing K. pneumoniae produces KPCs [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Carbapenemases are the main causes of multidrug resistance in CRKP and are classified into class A (KPC), class B (NDM, IMP, and VIM), and class D (OXA-48-like) [ 9 ]. In China and elsewhere, KPCs are major contributors to carbapenem resistance in K. pneumoniae and more than 70% of carbapenemase-producing K. pneumoniae produces KPCs [ 9–11 ].…”
Section: Introductionmentioning
confidence: 99%